Homology modeling, molecular dynamics, and virtual screening of NorA efflux pump inhibitors of Staphylococcus aureus - Bhaskar, Baki Vijaya; Babu, Tirumalasetty Muni Chandra; Reddy, Netala Vasudeava; Rajendra, Wudayagiri (Drug design, development and therapy, 2016)
Emerging drug resistance in clinical isolates of might be implicated to the overexpression of NorA efflux pump which is capable of extruding numerous structurally diverse compounds. However, NorA efflux pump is considered as a potential drug target for the development of efflux pump inhibitors. In the present study, NorA model was constructed based on the crystal structure of glycerol-3-phosphate transporter (PDBID: 1PW4). Molecular dynamics (MD) simulation was performed using NAMD2.7 for NorA which is embedded in the hydrated lipid bilayer. Structural design of NorA unveils amino (N)- and carboxyl (C)-terminal domains which are connected by long cytoplasmic loop. N and C domains are composed of six transmembrane α-helices (TM) which exhibits pseudo-twofold symmetry and possess voluminous substrate binding cavity between TM helices. Molecular docking of reserpine, totarol, ferruginol, salvin, thioxanthene, phenothiazine, omeprazole, verapamil, nalidixic acid, ciprofloxacin, levofloxacin, and acridine to NorA found that all the molecules were bound at the large hydrophobic cleft and indicated significant interactions with the key residues. In addition, structure-based virtual screening was employed which indicates that 14 potent novel lead molecules such as CID58685302, CID58685367, CID5799283, CID5578487, CID60028372, ZINC12196383, ZINC72140751, ZINC72137843, ZINC39227983, ZINC43742707, ZINC12196375, ZINC66166948, ZINC39228014, and ZINC14616160 have highest binding affinity for NorA. These lead molecules displayed considerable pharmacological properties as evidenced by Lipinski rule of five and prophecy of toxicity risk assessment. Thus, the present study will be helpful in designing and synthesis of a novel class of NorA efflux pump inhibitors that restore the susceptibilities of drug compounds.